Penerapan Pendekatan Saintifik Model CLCK untuk Meningkatkan Prestasi Belajar IPA Fisika Siswa Kelas IX - Arham Nur (Universtas Negeri Makassar, 2023)
The purpose of this study was to improve the learning achievement of students at MTs Negeri I Maros, Lau District, Maros Regency through learning the Application of the CLCK Model Scientific Approach to the Science of Physics subject. The research method used is this research is an action research, with stages of implementation including: (1) planning, (2) implementation, (3) observation and evaluation, (4) reflection. Based on the results of the study, it was obtained that the test cycle 1 did not show maximum results. The score was 63.25% or 3 students who scored 75-100. So the percentage of incompleteness is 59.25% or 17 students. Furthermore in cycle II it has shown that the results of learning mastery 75-100 are 84.75% or 18 students out of 20 students, so that learning mastery is less than 75%. So it was concluded that the application of the CLCK Guidance Model Scientific Approach can improve student learning achievement.